Is the synovial fluid cobalt-to-chromium ratio related to the serum partitioning of metal debris following metal-on-metal hip arthroplasty?. Issue 3 (March 2019) - Langton, D. J.; Natu, S.; Harrington, C. F.; Bowsher, J. G.; Nargol, A. V. F.
Abstract : Objectives: We investigated the reliability of the cobalt-chromium (CoCr) synovial joint fluid ratio (JFR) in identifying the presence of a severe aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL) response and/or suboptimal taper performance (SOTP) following metal-on-metal (MoM) hip arthroplasty. We then examined the possibility that the CoCr JFR may influence the serum partitioning of Co and Cr. Methods: For part A, we included all revision surgeries carried out at our unit with the relevant data, including volumetric wear analysis, joint fluid (JF) Co and Cr concentrations, and ALVAL grade (n = 315). Receiver operating characteristic curves were constructed to assess the reliability of the CoCr JFR in identifying severe ALVAL and/or SOTP. For part B, we included only patients with unilateral prostheses who had given matched serum and whole blood samples for Co and Cr analysis (n = 155). Multiple regression was used to examine the influence of JF concentrations on the serum partitioning of Co and Cr in the blood. Results: A CoCr JFR > 1 showed a specificity of 83% (77% to 88%) and sensitivity of 63% (55% to 70%) for the detection of severe ALVAL and/or SOTP. In patients with CoCr JFRs > 1, the median blood Cr to serum Cr ratio was 0.99, compared with 0.71 in patients with CoCr JFRs < 1 (p < 0.001). Regression analysis demonstrated that the blood Cr to serum Cr value was positively associated with the JF Co concentration (p = 0.011) and inversely related to the JF Cr concentration (p < 0.001). Conclusion: Elevations in CoCr JFRs are associated with adverse biological (severe ALVAL) or tribocorrosive processes (SOTP). Comparison of serum Cr with blood Cr concentrations may be a useful additional clinical tool to help to identify these conditions. Cite this article : D. J. Langton, S. Natu, C. F. Harrington, J. G. Bowsher, A. V. F. Nargol. Is the synovial fluid cobalt-to-chromium ratio related to the serum partitioning of metal debris following metal-on-metal hip arthroplasty? Bone Joint Res 2019;8:146–155. DOI: 10.1302/2046-3758.83.BJR-2018-0049.R1.